2015
DOI: 10.1242/jeb.114579
|View full text |Cite
|
Sign up to set email alerts
|

Distinct physiological strategies are used to cope with constant hypoxia and intermittent hypoxia in killifish (Fundulus heteroclitus)

Abstract: Many fish encounter hypoxia on a daily cycle, but the physiological effects of intermittent hypoxia are poorly understood. We investigated whether acclimation to constant (sustained) hypoxia or to intermittent diel cycles of nocturnal hypoxia (12 h normoxia:12 h hypoxia) had distinct effects on hypoxia tolerance or on several determinants of O 2 transport and O 2 utilization in estuarine killifish. Adult killifish were acclimated to normoxia, constant hypoxia, or intermittent hypoxia for 7 or 28 days in bracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 98 publications
10
97
3
Order By: Relevance
“…LDH is one of the enzymes of glycolytic pathway responsible for the anaerobic conversion of pyruvate to lactate, and it is ubiquitously present in most tissues. During the anaerobic metabolic shift, caused by hypoxia, there may be an up-regulation of LDH activities in different tissues (Borowiec, Darcy, Gillette, & Scott, 2015). The present study revealed an increase in LDH activity in both liver and muscle tissues after 72h of hypoxia exposure.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…LDH is one of the enzymes of glycolytic pathway responsible for the anaerobic conversion of pyruvate to lactate, and it is ubiquitously present in most tissues. During the anaerobic metabolic shift, caused by hypoxia, there may be an up-regulation of LDH activities in different tissues (Borowiec, Darcy, Gillette, & Scott, 2015). The present study revealed an increase in LDH activity in both liver and muscle tissues after 72h of hypoxia exposure.…”
supporting
confidence: 56%
“…The present study revealed an increase in LDH activity in both liver and muscle tissues after 72h of hypoxia exposure. However, muscle LDH remained unchanged after exposure to hypoxia in killifish Fundulus heteroclitus (Greaney, Place, Cashon, Smith, & Powers, 1980), However, there was an increase in activities of liver LDH in the above fish, Fundulus heteroclitus during hypoxic conditions (Borowiec et al, 2015). This may be due to an increase in lactate level during hypoxia, as lactate is the substrate for gluconeogenesis in liver.…”
mentioning
confidence: 87%
“…Remodelling of gill morphology has primarily been investigated in the context of acclimation to hypoxia (e.g. Crispo and Chapman, 2010), and this has been shown to occur via changes in the ILCM in a variety of fish species (Sollid et al, 2003(Sollid et al, , 2005aNilsson, 2007;Ong et al, 2007;Matey et al, 2008;Turko et al, 2012;Dhillon et al, 2013;Johannsson et al, 2014;Anttila et al, 2015) including killifish (Borowiec et al, 2015). Less is known about the effects of thermal acclimation on gill morphology, but decreases in the ILCM at warmer temperatures have been observed in crucian carp, goldfish (Sollid et al, 2005b;Mitrovic and Perry, 2009) and killifish (Barnes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several fish species live in environments with reduced O 2 availability and can tolerate prolonged and severe hypoxia (Stecyk et al, 2004;Scott et al, 2008;Richards et al, 2009;Speers-Roesch et al, 2012;Borowiec et al, 2015). Although mitochondrial abundance and respiratory capacity are known to vary substantially between fish species (Moyes et al, 1992), we are just beginning to appreciate the relationship between mitochondrial physiology and hypoxia tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia acclimation has often been shown to improve hypoxia tolerance (Fu et al, 2011;Dan et al, 2014;Borowiec et al, 2015) but the importance of changes in mitochondrial physiology to this process has not been well examined in fish, particularly in hypoxiatolerant species. Acclimation of mammals to moderate hypoxia (such as at high altitudes) reduces or has no effect on mitochondrial respiratory capacity (Costa et al, 1997;Nouette-Gaulain et al, 2005;Horscroft and Murray, 2014).…”
Section: Introductionmentioning
confidence: 99%